2022
DOI: 10.22146/ijp.3795
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of UV-visible and FTIR spectroscopy coupled with chemometrics for differentiation of Indonesian tea: an exploratory study

Abstract: Ultraviolet (UV)-visible and Fourier-transformed infrared (FTIR) spectroscopy are two of the most popular and readily available laboratory instruments. Fingerprinting analysis of the UV-visible and FTIR spectra has been applied for food classification and authentication studies. In this study, the UV-visible and FTIR spectra of brewed tea, and their data fusion data sets, were used to build models for the classification of tea based on tea types and origins. The study included black and green tea samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have reported the ability of near infrared (NIR) spectroscopy which works in the spectral range 13000–4000 cm −1 , to predict, with the help of multivariate calibration methods, the presence of different bioactive compounds in tea such as catechins, caffeine, free amino acids and theaflavins [ 10 , 11 , 12 , 13 , 14 , 15 ]; this technique has been also used to discriminate different tea varieties, also in relation with the geographical origins, and to identify tea grades and tea processing degree [ 10 , 16 , 17 , 18 ]. Conversely, to the best of our knowledge, only a few studies can be found in the literature regarding the use of FTIR spectroscopy in the MIR region (spectral range 4000–400 cm −1 ) to investigate tea leaves and tea brews and to highlight differences due to processing, cultivation site and extraction methods [ 4 , 16 , 18 , 19 , 20 , 21 , 22 ]. One advantage of FT-MIR spectroscopy is its ability to provide with one single acquisition the real chemical fingerprint of the analysed material, since it is very sensitive to the chemical composition of the sample as it contains the fundamental vibrations of almost all the functional groups [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the ability of near infrared (NIR) spectroscopy which works in the spectral range 13000–4000 cm −1 , to predict, with the help of multivariate calibration methods, the presence of different bioactive compounds in tea such as catechins, caffeine, free amino acids and theaflavins [ 10 , 11 , 12 , 13 , 14 , 15 ]; this technique has been also used to discriminate different tea varieties, also in relation with the geographical origins, and to identify tea grades and tea processing degree [ 10 , 16 , 17 , 18 ]. Conversely, to the best of our knowledge, only a few studies can be found in the literature regarding the use of FTIR spectroscopy in the MIR region (spectral range 4000–400 cm −1 ) to investigate tea leaves and tea brews and to highlight differences due to processing, cultivation site and extraction methods [ 4 , 16 , 18 , 19 , 20 , 21 , 22 ]. One advantage of FT-MIR spectroscopy is its ability to provide with one single acquisition the real chemical fingerprint of the analysed material, since it is very sensitive to the chemical composition of the sample as it contains the fundamental vibrations of almost all the functional groups [ 23 ].…”
Section: Introductionmentioning
confidence: 99%